Respuesta :

Answer:

+a = b-m-z

Step-by-step explanation:

Z = b-a-m

Collect like terms move -a to the left hand side and z to the right hand side -a becomes +a and z becomes -z

+a = b-m-z

Answer: [tex]a=\Large\boxed{-z-m+b}[/tex]

Step-by-step explanation:

Given expression

[tex]z=b-a-m[/tex]

Add [ m ] on both sides

[tex]z+m=b-a-m+m[/tex]

[tex]z+m=b-a[/tex]

Subtract [ b ] on both sides

[tex]z+m-b=b-a-b[/tex]

[tex]z+m-b=-a[/tex]

Multiply -1 on both sides

[tex](z+m-b)\times(-1)=-a\times(-1)[/tex]

[tex]a=\Large\boxed{-z-m+b}[/tex]

Hope this helps!! :)

Please let me know if you have any questions